Fenomena Politik Money dalam Perspektif Hadis - Syifaullah Syifaullah; Muhammad Alif (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
The phenomenon of money politics in the perspective of hadith and how the practice undermines the principles of justice, trustworthiness, and integrity in the democratic system, this study uses a descriptive qualitative approach with text analysis of relevant hadiths, and contextually studied in the frame of maqashid sharia. The results of the study show that money politics is included in the category of risywah (bribery) which is forbidden in Islam, as mentioned in various traditions of the Prophet Muhammad SAW. This practice has serious impacts, including damage to the government system, loss of legitimacy of leaders, and threats to social stability. Therefore, Islam emphasizes the importance of rejecting money politics as part of the moral and spiritual responsibility of the people. Moral education, the role of religious leaders, and strengthening regulations are important parts of the prevention strategy. This research recommends a synergy between state institutions and religious institutions in building a clean, fair, and political system based on Islamic ethics.